Kemampuan Berpikir Kreatif Mahasiswa dalam Menyelesaikan Soal-soal Open-Ended - Hoiriyah, Diyah (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2019)
The purpose of this study is to describe the creative thinking ability of Tadris/ Mathematics Education students in Padangsidimpuan IAIN in solving open-ended problems. The approach used is a descriptive qualitative approach that seeks to analyze the ability of students to think creatively in solving open-ended problems. The research subjects were students of the third semester of the Tadris / Mathematics Education Study Program at IAIN Padangsidimpuan. The research subjects consisted of 6 students consisting of 2 students in the high category, 2 students in the medium category, and 2 students in the low category. Data collection techniques in the form of observation, tests and interviews. Data analysis is performed by data reduction, data presentation and verification or conclusions. The data validity technique is done by triangulating data sources. The results showed that students' creative thinking ability for high category was very good in solving open-ended mathematics problems. The ability of students to think creatively for the category is in good criteria. The ability of students to think creatively for low categories as a whole is in poor criteria. Overall for low ability students still need coaching.